Material didáctico en la enseñanza y aprendizaje de las tablas de multiplicar en cuarto grado de la escuela “Miguel Riofrío”, periodo 2023-2024 - Gallegos Peña, Gabriela Alexandra (2024)
The didactic material in the teaching and learning of multiplication tables plays a crucial role in the mathematical development of students, this type of resources not only facilitates the memorization of the tables, but also promotes understanding through visual, interactive and practical methods, thus strengthening their skills in a significant way. As general objective, it was proposed to determine the incidence of the didactic material in the teaching and learning process of multiplication tables in fourth grade students of "Miguel Riofrio" School, period 2023-2024. And as specific objectives the following were proposed: To identify the didactic material currently used in the process of teaching and learning of multiplication tables in fourth grade students; To propose innovative didactic material for the process of teaching and learning of multiplication tables in fourth grade students; and To evaluate the incidence of the proposed didactic material considering the contribution to the improvement of teaching and learning of multiplication tables. This study was conducted under a descriptive, non-experimental, quantitative approach. The hermeneutic, inductive, deductive, analytical, synthetic and statistical methods were used. The techniques: observation and survey; the instruments: questionnaire and observation form; and the procedures: diagnosis, theoretical foundation and the design of the pedagogical proposal, taking as a reference the results that were diagnosed in the observation. It should be noted that we worked with the entire population, which is made up of 15 students and 3 teachers, showing that the use of didactic material used has a positive influence on student learning, encouraging greater active participation in the classroom and promoting the development of critical thinking.